Penegakkan Yurisdiksi International Criminal Court atas Kejahatan Agresi Pasca Kampala Amendments Diadopsi dalam Rome Statute - Irham, Apripari (Faculty of Law, Universitas Pattimura, 2020)
Until the entry into force of the Rome Statute, the definition of the crime of aggression was not also found in it. This leaves the International Criminal Court (ICC) without jurisdiction over crimes of aggression. The absence of ICC jurisdiction over crimes of aggression has resulted in military aggression that has not been processed by the ICC during the time when the proxy war / cold war was initiated. This means that the violation of delicto jus gentium juice is allowed even after the ICC has been established. This study aims: (1) to identify and identify the definition, limitations, and jurisdiction of the ICC for crimes of aggression; and (2) to determine the enforcement of ICC jurisdiction over crimes of aggression after the Kampala Amendments were adopted into the Rome Statute. The research method uses a type of normative research with a statutory approach and a historical approach. The results show that the ICC's definition, limitations, and jurisdiction over the crime of aggression have existed in the Rome Statute since Kampala Amendments were adopted into the Rome Statute. However, until now the enforcement of the ICC's jurisdiction over crimes of aggression has not been carried out concretely.